Time-resolved studies of the early hydration of cements using synchrontron energy-dispersive diffraction - Barnes, P.; Clark, S. M.; Hausermann, D.; Fentiman, C.; Muhamad, M. N.; Rashid, S. (1992)
We outline the need to study the early hydration of cements by dynamic diffraction methods, and demonstrate how this can be done using a â€œhydration cellâ€ designed specifically for the parallel beam geometry of synchrotron energy-dispersive diffraction. The method has been applied to three systems: a model component of portland cement, a high-alumina cement and an ettringite-based cement. The results show how this technique might be used to gather information on the kinetics of the chemical processes involved. In the case of ettringite, we can follow dynamically the crystallisation process on an unprecedented 20 second time scale.